Identification of biorelevant dissolution media to assess biopharmaceutical performance of erlotinib formulation with enhanced bioavailability using physiologybased pharmacokinetic modeling - Chandra, Amrish (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The aim of the present work was to predict the bioavailability (BA) of poorly soluble drug. In vitro dissolution of selected BCS Class II drug was conducted in different dissolution media to identify the discriminatory behaviors of the dissolution media. Further, the development of physiology-based pharmacokinetic modeling performed using GastroPlus® for BA predictions of formulation showing enhanced dissolution. Study Design: Using GastroPlus® software (Simulations Plus, Lancaster, CA), a physiology-based pharmacokinetic model for erlotinib was developed. Erlotinib absorption was described using the advanced compartmental absorption and transit model. The input parameters for the simulation were either determined experimentally or gathered from the literature. Place and Duration of Study: Amity Institute of Pharmacy, Noida. Methodology: In vitro dissolution studies were conducted and data were analyze to find the biorelevent dissolution media. GastroPlus® model was built to predict the Cmax and AUC and also was validated for the prediction error <10%. Validated model was used to predict the BA parameters of optimized formulation using the dissolution profile. Results: Based on predicted T/R ratio, it is observed that optimized formulation shows approximately ~ 25% higher rate of absorption and bioavailability. Conclusion: Erlotinib tablet formulation was prepared using micronized drug substance, optimized formulation was subjected to various dissolution tests and biorelevent media was identified based on best fit/correlation with the deconvulated profile, which was further used for simulation modeling and BA prediction. Micronization can be used as a technique to enhance the drug dissolution of BCS Class II drugs and corresponding BA. IVIVR GastroPlus modeling and simulations can be useful tool to assess the biopharmaceutical performance for initial screening and further taking up the optimized formulation for clinical studies.